ANALISIS JUMLAH KENDARAAN BERMOTOR DI DAERAH ISTIMEWA YOGYAKARTA (1990–2012) - Wantara, I Agus (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2015)
In the last few years, traffic congestions are often occurred in Yogyakarta. This situation is caused byÃ‚Â the increasing number of vehicles in Yogyakarta.This study evaluates the effect of the gross regional domesticproduct (PDRB), the people of Daerah Istimewa Yogyakarta (JP), and region income (PD) to the number ofÃ‚Â vehicles in Daerah Istimewa Yogyakarta (JKB). The model consists of one behavioral equation: the numberÃ‚Â of vehicles equation. The estimation technique uses Ordinary Least Squares (OLS). MacKinnon, White, andÃ‚Â Davidson test (MWD test) is used to choose between the two models: linear regression model or log-linearregression model.The sample covers observations for 23 years (1990 - 2012). The data are obtained from (1)Ã‚Â Bank Indonesia (2) Badan Pusat Statistik DIY and various other sources. It is found that individually lnJP andlnPD are statistically significant (positive) except ln PDRB on the basis of (separate) t test. It is also found that onÃ‚Â the basis of the F test collectively all the regressors have a significant effect on the regressand lnJKB.Keywords: the number of vehicles, traffic congestion, linear regression model, log-linear regression model.